The Effect of Audit Quality, Corporate Governance and CSR on Real Earning Management: Indonesian Evidence - Mahmudi Mahmudi; Arief Bahtiar; Afvia Duhita (Iranian Journal of Accounting, Auditing & Finance, 2024)
This study investigates the effect of audit quality, corporate governance, and Corporate Social Responsibility (CSR) on real earnings management. This study proxies corporate governance by audit committee size, independent commissioner proportion, managerial ownership, and institutional ownership. The population in this study is the manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019-2021. The sampling method was carried out using a purposive sampling approach. This study obtained 236 observation data from 82 companies in Indonesia. The data was analyzed using regression analysis. The results of this study indicate that audit quality, managerial ownership and institutional ownership positively affect real earnings management. At the same time, the audit committee has a negative significant effect on real earnings management. However, the proportion of independent boards of commissioners and Corporate Social Responsibility disclosure does not affect real earnings management. This research shed light on the role of corporate governance mechanisms and CSR in real earnings management practices of Indonesian public companies.